Limited Liability Partnerships (LLP) and Business Groups in India: A Law and Economics Analysis - Gupta, Mohit Kumar (H. : ĐHKT, 2020)
The Limited Liability Partnership Act, 2008 (hereafter LLP Act, 2008) was enforced in Indian jurisdiction from the year 2009. The said Act allowed for the creation of Limited Liability Partnership (LLP) as a hybrid entity which embodied the features of both traditional partnership (in terms of ease of management and operation) as well as company form (limited liability). It was introduced in the backdrop of demand by various expert committees and professional bodies to assist the growth of professional bodies in India for instance doctors, lawyers, charted accountant firms etc. This was in so far as there is the Indian Partnership Act, 1932 for catering the needs of small trading firms while the Companies Act, 2013 caters to the need of relatively larger business. However, there was a lacuna as well as these medium-sized professional firms were concerned. Their expansion in an era of globalisation was curtailed by the disadvantage of unlimited liability in a partnership firm and the complexities of disclosures and management associated with the company form. However, this study shows that how the LLP has gone beyond this stated objective of assisting the growth of professional firms only and is being used by the corporate sector in India towards meeting their desired objectives like tax evasion, organising complex group structure etc. In the process, it fleshes out the lacunae in the Income Tax Act, 1961, Companies Act, 2013 and the antitrust legislation, i.e. the Competition Act, 2002 that allows for such a use of LLP by business groups in India.